Superior Venacava Thrombus-A Case Report - Sah, Bijay; Shrestha, Krishna Gopal; Tiwari, Kaushal Kishor; Reddy, D. Jayapal (Journal of College of Medical Sciences-Nepal, 2016)
Superior venacava (SVC) thrombus is a condition requiring immediate diagnosis and treatment. SVC thrombus causes obstruction of blood flow through the SVC resulting in severe decrease in venous return from the head, neck and upper extremity to the heart. The presenting symptoms of SVC obstruction include headache, hoarseness of voice, dyspnea, and laryngeal edema, dizziness, swelling of face, neck, and upper extremity. We hereby present a case of SVC thrombus who presented to the casualty department of COMS-TH with features of SVC syndrome which was diagnosed and managed promptly. JCMS Nepal. 2016;12(1):33-5.